2023
DOI: 10.1111/obr.13550
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and weight change during the COVID‐19 pandemic in children and adults: A systematic review and meta‐analysis

Abstract: Many obesity risk factors have increased during the COVID-19 pandemic, including physical inactivity, poor diet, stress, and poverty. The aim of this systematic review was to evaluate the impact of the COVID-19 pandemic, as well as associated lockdowns or restrictions, on weight change in children and adults. We searched five databases from January 2020 to November 2021. We included only longitudinal studies with measures from before and during the pandemic that evaluated the change in weight, body mass index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 150 publications
(380 reference statements)
4
38
0
2
Order By: Relevance
“…Recent COVID-19 lockdowns upended our daily routines, including feeding behavior, with at least part of the population showing See accompanying article, pg. 1000. significant weight increases [6] that may be linked to increases in diets higher in fat.…”
Section: Migration Studies Have Provided Another Interesting Window Onmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent COVID-19 lockdowns upended our daily routines, including feeding behavior, with at least part of the population showing See accompanying article, pg. 1000. significant weight increases [6] that may be linked to increases in diets higher in fat.…”
Section: Migration Studies Have Provided Another Interesting Window Onmentioning
confidence: 99%
“…The Ni‐Hon‐San study, conducted in the 1970s before the drastic worldwide rise in obesity rates, looked at the risk factors for cardiovascular disease in Japanese men living either in Hiroshima, Japan; Honolulu, Hawaii; or San Francisco, California [5]. The diets from these three regions differed drastically, with the California diet having a significantly higher percentage of fat (38%) than the Japanese diet (15%) that correlated with significantly higher body weight (66 kg in California and 55 kg in Japan; +22%) and an elevated risk of cardiovascular heart disease. Recent COVID‐19 lockdowns upended our daily routines, including feeding behavior, with at least part of the population showing significant weight increases [6] that may be linked to increases in diets higher in fat.…”
mentioning
confidence: 99%
“…Obesity is a major public health concern with increasing incidence and prevalence over the last four decades worldwide. [1][2][3] Between 1.0% and 5.5% of children and adolescents are living with severe obesity, which is often accompanied by comorbidities, such as type 2 diabetes mellitus (T2DM) and psychological comorbidities. [4][5][6] Obesity in childhood often transitions into adulthood, indicating the chronic nature of the disease and emphasizing the need for comprehensive, effective and safe treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a major public health concern with increasing incidence and prevalence over the last four decades worldwide 1–3 . Between 1.0% and 5.5% of children and adolescents are living with severe obesity, which is often accompanied by comorbidities, such as type 2 diabetes mellitus (T2DM) and psychological comorbidities 4–6 …”
Section: Introductionmentioning
confidence: 99%
“…Although there are mixed findings on whether unhealthy changes in diet emerged during the pandemic, most studies between 2020 and 2022 have nevertheless observed increases in overweight and obesity. 6 The decreases in physical activity and presence of other factors, such as stress, may underlie these disconcerting changes. Rates of overweight and obesity were already on the upswing before the PHE, yet the pandemic may have accelerated that pattern.…”
mentioning
confidence: 99%